The millipedes (Diplopoda) in Yintiaoling National Natural Reserve, Southwest China - Chen, Hui-Ming; Zheng, Chang-Bin; Jiang, Xuan-Kong (Zootaxa, 2023)
The millipedes of Yintiaoling National Natural Reserve, Southwest China, were investigated. In total, thirteen species from five orders (Sphaerotheriida, Spirobolida, Callipodida, Chordeumatida and Polydesmida) and eight families were discovered. Among them, six species are new to science: Zephronia linkouzi sp. nov., Paracortina inflata sp. nov., Orthomorpha laminata sp. nov., Polylobosoma corollifera sp. nov., Epanerchodus wuxi sp. nov. and Riukiaria spina sp. nov. As usual, the polydesmidan family Paradoxosomatidae is the most diverse group, containing five species. All new species are described and illustrated, and photographs of the habitus and the gonopods of all species are also provided.